(untitled) (International Journal of Engineering and Computer Science, 2018)
If the teacher was able to clarify to students what is the purpose of the lecture? What they will learn? How to build and construct what they learn by themselves? If the students were able to answer similar questions; that would increase their chance to understand the lecture. The main goal of this study is review the curriculum of the cores to nd any potential problem and suggest a solution for such limitation then analyze the impact of that solution on the knowledge of students. Furthermore, this paper presents a result of a real study of the impact of changing teaching method from traditional method to teaching with discussion technique and who that re ected on the level of students.